Global patterns in wood carbon concentration across the world's trees and forests. Issue 12 (December 2018) - Martin, Adam; Doraisami, Mahendra; Thomas, Sean
Abstract Wood carbon concentrations play a central role in forest carbon accounting, and are fundamentally linked to the growth strategies of woody plants. Yet there are no comprehensive assessments of wood carbon among trees globally, and coarse approximations of wood carbon (for example, 50%) are employed in virtually all benchmark models and assessments of forest carbon. We consolidated the largest database for any wood chemical trait—2, 228 wood carbon observations from 636 species across all forested biomes—to derive robust wood carbon fractions for forest carbon accounting. Carbon fractions show substantial variation among forest biomes, and indicate errors in the existing forest carbon estimates of 4.8%, on average, and most extreme errors of 8.9% in tropical forests. The data also demonstrate that wood carbon concentrations show a phylogenetic signal and are co-evolved with, and negatively related to, wood density, thus representing a key plant trait that links plant functional biology to ecosystem processes worldwide. Large variability of wood carbon fractions in different trees can lead to an error of up to 8.9% in carbon estimates for forests, according to an analysis of wood carbon data across global forested biomes.